Updated Diagnosis Grouping System for Pediatric Emergency Department Visits. Issue 5 (25th May 2023) - Fant, Colleen; Marin, Jennifer R.; Ramgopal, Sriram; Simon, Norma-Jean E.; Richards, Rachel; Olsen, Cody S.; Alessandrini, Evaline A.; Alpern, Elizabeth R.; ,
Abstract : Objectives: This study aims to update the Diagnosis Grouping System (DGS) for International Classification of Disease, Tenth Revision ( ICD-10 ) codes for ongoing use. The DGS was developed in 2010 using ICD-9 codes with 21 major groups and 27 subgroups to facilitate research on pediatric patients presenting to emergency departments and required updated classification for more recent ICD codes. Methods: All emergency department discharges available in the Pediatric Emergency Care Applied Research Network (PECARN) database for 2016 were included to identify ICD-10 codes. These codes were then mapped onto the DGS codes originally derived from ICD-9 . We used ICD-10 codes from the PECARN database from 2017 to 2019 to confirm validity. Results: The DGS was updated with ICD-10 codes based on 2016 PECARN data, and this updated DGS was successfully applied to 6, 853, 479 (97.3%) of all codes from 2017 to 2019. Discussion: Using ICD-10 codes from the PECARN Registry, the DGS was updated to reflect ICD-10 codes to facilitate ongoing research.